A pesca como um problema de segurança: limites e possibilidades para a cooperação internacional no Oceano Austral - Vaz Ferreira, Luciano (Revista InterAção, 2018)
With fish stocks around the world on the verge of collapse, with immeasurable environmental, economic and social consequences, the possibilities for proliferation of IUU fishing (illegal, unreported or unregulated) have come under close scrutiny by the international community. In this context, processes of securitization of the problem were triggered. The Southern Ocean is particularly vulnerable to IUU fishing, and may be a stage for new security dynamics. In this context, the following research problem is presented: "In what way do the dynamics of securitization of fisheries control in the Southern Ocean occur and what is the role of international cooperation in this process?" Besides the answer to the research problem, which is the general objective, the article aims to investigate the securitization of fishing in the international scenario, to study the security dynamics in the Southern Ocean, to discuss the roles of cooperation and international regimes in this process . The research is exploratory in nature. As a research technique the bibliographic review was chosen, using interdisciplinary material and documentary analysis. Com os estoques pesqueiros ao redor do mundo à beira do colapso, com consequências ambientais, econômicas e sociais imensuráveis, as possibilidades de proliferação da pesca INN (ilegal, não declarada ou não regulamentada) passaram a ser acompanhadas com grande atenção pela comunidade internacional. Neste contexto, desencadearam-se processos de securitização do problema. O Oceano Austral é particularmente vulnerável à pesca INN, podendo ser palco de novas dinâmicas de segurança. Neste contexto, apresenta-se o seguinte problema de pesquisa: “de que maneira ocorrem as dinâmicas de securitização do controle da pesca no Oceano Austral e qual o papel da cooperação internacional neste processo”? Além da resposta ao problema de pesquisa, que é o objetivo geral, o artigo possui como objetivos específicos investigar a securitização da pesca no cenário internacional, estudar as dinâmicas de ...